2018
DOI: 10.21037/jovs.2017.12.06
|View full text |Cite
|
Sign up to set email alerts
|

Chronic type B “residual” after type A: what I would do?

Abstract: "" This motto still remains the most important directive. However, also depending onto the extent of the underlying pathology and consecutively depending onto the extent of primary surgery, there is and will be need for additional classical surgical or interventional treatment sooner or later during follow-up in a substantial number of patients having had surgery for acute type A aortic dissection. This article shall guide the interested reader through the underlying mechanisms as well as treatment options in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[1][2][3] It provides a proximal platform for second-stage endovascular or surgical (ie, thoracoabdominal) repair and may potentially be used to treat the thoracic aorta in 1 single step. 3,4 Although the FET technique facilitates positive remodeling in downstream aortic segments in a variety of different aortic pathologies, the need for aortic reinterventions following the FET procedure and the potential of the FET technique to truly be a single-step procedure to treat the thoracic aorta remain unclear. [5][6][7] Therefore, the aim of this study was to evaluate the need and outcomes of aortic reinterventions after previous FET implantation.…”
Section: Perspectivementioning
confidence: 99%
“…[1][2][3] It provides a proximal platform for second-stage endovascular or surgical (ie, thoracoabdominal) repair and may potentially be used to treat the thoracic aorta in 1 single step. 3,4 Although the FET technique facilitates positive remodeling in downstream aortic segments in a variety of different aortic pathologies, the need for aortic reinterventions following the FET procedure and the potential of the FET technique to truly be a single-step procedure to treat the thoracic aorta remain unclear. [5][6][7] Therefore, the aim of this study was to evaluate the need and outcomes of aortic reinterventions after previous FET implantation.…”
Section: Perspectivementioning
confidence: 99%
“…The mean delay between the 2 procedures was 52.1 days (0-214 days). The mean proximal landing zone diameter was 32.6 mm (28-40), the mean proximal stent graft diameter was 37.7 mm (32-45 mm), the mean aortic coverage was 239.5 mm (115-340), and the mean oversizing was 15.6% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Since 2017, we have treated 7 patients with the STABILISE technique when the maximum aortic diameter on the thoraco-abdominal aorta was less than 42 mm.…”
Section: Tevarmentioning
confidence: 99%
“…There are no guidelines regarding the treatment of distal aneurysmal degeneration of chronic RAD. Open surgery with total arch replacement, frozen elephant trunk (FET), hybrid treatment with supra-aortic trunk debranching and TEVAR, or total endovascular solution with fenestrated/branched endoprosthesis are different options [13].…”
Section: Commentmentioning
confidence: 99%
“…Ma et al published their experience with 132 FET procedures in the acute phase with a stroke rate of 5.3% and a 30-day mortality rate of 14.4%. 6,7 However, there is still no definite and clear consensus on the indication of the FET during the index operation. Poon et al proposed the FET operation in the acute phase only in the high-volume centers because they found a similar mortality for FET and less invasive index operations (ascending replacement or hemi-arch repair).…”
Section: Frozen Elephant Trunkmentioning
confidence: 99%
“…A recently published study by Ma et al found better survival in the octogenarian acute type A dissection patients for the debranching procedure compared with FET. 7 Patients with chronic dissections were excluded from their analysis. Bavaria et al demonstrated the safety of complete debranching in a cohort of mainly aneurysm patients (arch dissections 11%) with a procedural success of 100% on CPB.…”
Section: Hybrid Proceduresmentioning
confidence: 99%